Pola Asuh dan Peran Orang Tua dalam Mendukung Pendidikan Anak; Perspektif Pendidikan Ekonomi Informal - Dian Nur Elisa (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze parenting patterns and the role of parents in supporting children's education from the perspective of informal economic education in the family environment. Using a qualitative phenomenological approach, data were collected through observation, in-depth interviews, and documentation of 10 informants in Sukoanyar Village, Cerme District, Gresik Regency. The results of the study indicate that parenting patterns applied by parents vary greatly, ranging from democratic, authoritarian, permissive, to situational, with a tendency for democratic patterns to have a positive impact on children's economic independence and responsibility. The role of parents as role models and first educators in the family has proven crucial in instilling economic values ​​through example, communication, and active involvement in household financial management. Data analysis using the NVivo 12 application strengthens the finding that informal economic education in the family shapes children's character and economic behavior in a sustainable manner. This study emphasizes the importance of active parental participation in informal economic education to build a foundation for financial literacy and a responsible attitude in children from an early age.